2015
DOI: 10.1523/jneurosci.2731-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Feedforward and Feedback Motor Control Abnormalities Implicate Cerebellar Dysfunctions in Autism Spectrum Disorder

Abstract: Sensorimotor abnormalities are common in autism spectrum disorder (ASD) and among the earliest manifestations of the disorder. They have been studied far less than the social-communication and cognitive deficits that define ASD, but a mechanistic understanding of sensorimotor abnormalities in ASD may provide key insights into the neural underpinnings of the disorder. In this human study, we examined rapid, precision grip force contractions to determine whether feedforward mechanisms supporting initial motor ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
143
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(172 citation statements)
references
References 95 publications
25
143
2
2
Order By: Relevance
“…Abnormality of these regions may have a distinct influence on motor impairment in ASD. For example, although the S1-M1 connections likely play a role in sensory feedback after contact with an object, anterior cerebellar abnormalities may be associated with deficits in the feedforward planning, which occurs before object contact (58). A more comprehensive assessment of the tracts involved in motor planning and execution, which may also include, for example, the superior cerebellar peduncle and the superior longitudinal fasciculus system, will be necessary to understand the specific role of each tract to fine motor skills in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormality of these regions may have a distinct influence on motor impairment in ASD. For example, although the S1-M1 connections likely play a role in sensory feedback after contact with an object, anterior cerebellar abnormalities may be associated with deficits in the feedforward planning, which occurs before object contact (58). A more comprehensive assessment of the tracts involved in motor planning and execution, which may also include, for example, the superior cerebellar peduncle and the superior longitudinal fasciculus system, will be necessary to understand the specific role of each tract to fine motor skills in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…The precision grip task studied here has been employed in previous investigations to understand how the neural control of voluntary movement is impaired in Autism Spectrum Disorders (ASD) (Mosconi et al 2015; Wang et al 2015), Parkinson’s disease (Vaillancourt et al 2001) and atypical parkinsonian disorders (Neely et al 2013b), and essential tremor (Neely et al 2015; Poon et al 2011). Visual stimuli were presented on a 102 cm (40-inch) Samsung television screen with resolution 1920 × 1080 and a 120 Hz refresh rate.…”
Section: Methodsmentioning
confidence: 99%
“…In a pair of studies examining precision gripping, we reported that individuals with ASD make less accurate initial force contractions and show increased variability of sustained force output despite similar levels of overall force relative to controls (Mosconi et al 2015; Wang et al 2015). These findings suggest that the internal action representation used for feedforward control (i.e., the initial contraction) may not be accurate in individuals with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the finding that individuals with ASD produce greater variability during sustained force implicates the online visuomotor mechanisms involved in translating visual feedback into corrective motor commands. Importantly, the variability in sustained force increased further when visual feedback was reduced (Mosconi et al 2015). Taken together, these findings demonstrate that individuals with ASD may have inaccurate internal representations to plan force output and may also be more reliant on visual feedback to make adjustments during sustained force output.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation